2000
DOI: 10.1021/jf990891y
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of Ochratoxin A and Citrinin in Cereals from Bulgarian Villages with a History of Balkan Endemic Nephropathy

Abstract: Cereal samples were collected in 1998 from Bulgarian villages without [control village (C), n = 20] or with [endemic villages (E); E1, n = 21; E2, n = 30; E3, n = 23] a history of Balkan endemic nephropathy (BEN). Sampling included foods (wheat, corn) and feeds (barley, oats, wheat bran). Analysis of ochratoxin A and citrinin was done by enzyme immunoassays (EIA), with detection limits of 0.5 and 5 ng/g, respectively. Ochratoxin A-positive results were confirmed by HPLC after immunoaffinity chromatography. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
2
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(110 citation statements)
references
References 21 publications
8
96
2
2
Order By: Relevance
“…180-580 ng/g [36]. CTN contamination has additionally been reported in Monascus fermentation products [29,37] used as food colourants and flavour enhancers in the Orient, and as dietary supplements believed to prevent heart disease and decrease plasma triacylglycerol and cholesterol levels [38].…”
Section: Discussionmentioning
confidence: 99%
“…180-580 ng/g [36]. CTN contamination has additionally been reported in Monascus fermentation products [29,37] used as food colourants and flavour enhancers in the Orient, and as dietary supplements believed to prevent heart disease and decrease plasma triacylglycerol and cholesterol levels [38].…”
Section: Discussionmentioning
confidence: 99%
“…Ochratoxin A (OA) is mainly produced by fungi Aspergillus and Penicillium genus (50), where A. ochraceus (Wilhelm) and P. verucosum (Dierckx) are the main productive species of this mycotoxin. Ochratoxin A (OA) is mutagenic, teratogenic and nephrotoxic and has been involved in etiology of Balkan Endemic Nephropathy (7).…”
Section: Zummo and Scottmentioning
confidence: 99%
“…This mycotoxin is produced mainly by the mould fungi Aspergillus ochraceus and Penicillium verrucosum that grow on cereal grains and other plant-derived products during storage at 15-19% moisture content and temperatures exceeding 15 °C (Abramson et al, 1992). OTA contamination occurs in barley (Scudamore et al, 1997), wheat (Vrabcheva et al, 2000), maize (Scudamore and Patel, 2000) and other cereals (Jorgensen et al, 1996) with a prevalence and intensity that vary by year and by country. In Hungary, 14-15% of the feeds analysed in the 1970s was found to contain OTA (Sándor et al, 1982).…”
Section: Acta Veterinaria Hungarica 50 2002mentioning
confidence: 99%
“…Its nephrotoxic effect in pigs was first reported by Larsen (1928). Although numerous data suggest that the so-called 'Balkan endemic nephropathy', the longknown disease associated with chronic nephropathy in humans, is caused by OTA, the aetiology of this disease cannot be considered fully clarified yet (Vrabcheva et al, 2000;Puntaric et al, 2001). Studies conducted in recent years have demonstrated that OTA has carcinogenic, teratogenic and immunotoxic effects (Huff, 1991;Kuiper-Goodman, 1991;Petzinger and Ziegler, 2000).…”
Section: Acta Veterinaria Hungarica 50 2002mentioning
confidence: 99%